Use Of Special Exercises In Developing The Strength Of Wrestlers (Eurasian Medical Research Periodical, 2025)
This article discusses the effective organization of the training process through the effective use of special tools to improve the physical, technical-tactical and psychological preparation of wrestlers, and to develop the quality of strength.